Comparison of two tube-modification techniques in baerveldt glaucoma implantation in refractory glaucoma - Purit Petpiroon (2020)
© 2020 Petpiroon et al. This work is published and licensed by Dove Medical Press Limited. Importance: To compare treatment outcomes among a stent group, ligature group and combined groupineyeswithrefractoryglaucoma. Background: Various techniques have been used intra-operatively to restrict the aqueous flow in Baerveldt glaucoma implantation. Design: Retrospective chart review. Participants: All glaucoma patients aged over 18-years old who had Baerveldt implantation in Ramathibodi Hospital, Bangkok, Thailand, between October 2011 and February 2018 were included for analysis. Methods: Retrospective interventional research was conducted. All glaucoma patients who underwent drainage device implantations were retrospectively reviewed from medical records and divided into three groups: stent group, ligature group, and combined group. The primary outcome was post-operative intraocular pressure (IOP) changes and BCVA (logMAR) change. The secondary outcome is treatment failure. Repeated measurements with mixed models and multi-level parametric survival model stratified by propensity score and eye side were used to compare the primary and secondary outcomes between stent group and ligature group. Main Outcome Measures: Treatment failure between two groups. Results: A total of 163 patients with a mean age of 57.11 ± 19.04 years, implanted with Baerveldt tube, were eligible. There were no significant differences between stent and ligature groups in terms of post-operative IOP changes [mean difference with 95% confidence interval = 0.53 (−0.49, +1.55) vs −0.02 (−0.84, +0.81); P = 0.411] and post-operative BCVA (logMAR) change (0.02 (−0.13, +0.18) vs –0.05 (−0.18, +0.07); P = 0.465). The hazard ratio and 95% confidence interval of treatment failure in ligature group were 2.57 (0.72–9.19) compared with the stent group. Conclusion: This study suggests a trend toward a better result in the stent group compared with the ligature group. Further research with a larger sample size and randomized control trial is warranted.